2004
DOI: 10.1038/sj.npp.1300481
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Activates Reward Circuitry in Drug Naïve Human Subjects

Abstract: Amphetamines are highly addictive drugs that have pronounced effects on emotional and cognitive behavior in humans. These effects are mediated through their potent dopaminergic agonistic properties. Dopamine has also been implicated in the modulation of responses of the 'reward circuit' in animal and human studies. In this study we use functional magnetic resonance imaging (fMRI) to identify the brain circuitry involved in the psychostimulant effect of methamphetamine in psychostimulant-naïve human subjects. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(84 citation statements)
references
References 43 publications
6
77
0
1
Order By: Relevance
“…These findings suggest that pharmacodynamic adaptations, which occurred during the course of continuous drug exposure, might account for the apparent dissociation between the plasma drug levels and behavioral activity at these later time intervals. Several clinical researchers have speculated that the acute tolerance might be due to DA depletion at critical brain sites and/or downregulation of DA receptors (Angrist, 1987;Vollm et al, 2004). In this regard, our results showed that the acute striatal extracellular DA response was significantly shorter than would be expected from the pharmacokinetic data, and therefore, this apparent pharmacodynamic alteration could, at least partially, underlie the acute tolerance reflected in the measure of behavioral activation we monitored.…”
Section: Behavioral Profilesupporting
confidence: 47%
See 1 more Smart Citation
“…These findings suggest that pharmacodynamic adaptations, which occurred during the course of continuous drug exposure, might account for the apparent dissociation between the plasma drug levels and behavioral activity at these later time intervals. Several clinical researchers have speculated that the acute tolerance might be due to DA depletion at critical brain sites and/or downregulation of DA receptors (Angrist, 1987;Vollm et al, 2004). In this regard, our results showed that the acute striatal extracellular DA response was significantly shorter than would be expected from the pharmacokinetic data, and therefore, this apparent pharmacodynamic alteration could, at least partially, underlie the acute tolerance reflected in the measure of behavioral activation we monitored.…”
Section: Behavioral Profilesupporting
confidence: 47%
“…Controlled studies in humans have shown that acute administration of low AMPH doses produces subjective effects like euphoria, 'mind racing', and alertness Angrist, 1987;McTavish et al, 1999;Vollm et al, 2004); physiological changes in heart rate and blood pressure have also been monitored (Griffith and Gunne, 1977;Brown et al, 1978;Angrist et al, 1987;Angrist, 1987;Cook et al, 1993;Oswald et al, 2005). In many of these studies, when the time course of these stimulant-induced alterations was determined, a dissociation between these effects and measured or inferred plasma levels was apparent and often referred to as acute tolerance or tachyphylaxis Angrist, 1987;Cook et al, 1993;Swanson et al, 2002;Greenhill et al, 2003;Foltin and Haney, 2004).…”
Section: Behavioral Profilementioning
confidence: 99%
“…Correlated cerebral blood flow changes were observed in the orbitofrontal cortex, in addition to the ventral striatum, the amygdala, and the ventromedial prefrontal cortex. Vollm et al (2004) used highly addictive drugs, amphetamines, to drug naïve human subjects and examined correlations between brain activation measured by fMRI and subjective ratings of "mind-racing," which was defined as "a state where your thoughts run far too quickly as if they were racing. One thought is replaced by another very quickly and it is difficult to hold on to your thought."…”
Section: Orbitofrontal Cortexmentioning
confidence: 99%
“…More specifically, the major depression symptom of anhedonia, characterized by reward-insensitive behavior and blunted positive emotionality -and hence, apparently, the extremely low end of aE (Depue, 1995) -has been associated with abnormally low levels of activity in the ventral-rostral ACC (rACC) regions (Pizzagalli, Peccoralo, Davidson, & Cohen, 2006) and with blunted nucleus accumbens responses to reward signals (Wacker, Dillon, & Pizzagalli, 2009). Furthermore, pharmacological challenge studies have demonstrated that the ACC responds to dopaminergic drugs (e.g., Völlm et al, 2004), and ACC activity also qualifies as a predictor for psychopharmacological treatment responses (for selective norepinephrine and serotonin reuptake inhibitors, see Korb, Hunter, Cook, & Leuchter, 2009).…”
Section: Agentic Extraversion and Anterior Cingulate Cortex Activitymentioning
confidence: 99%